2009
DOI: 10.1007/s10461-009-9540-3
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Trial of an Intervention Aimed at Modifying Drug Preparation Practices Among Injection Drug Users in Puerto Rico

Abstract: Injection drug users (IDUs) contaminate preparation materials with blood-borne pathogens by using syringes as measuring and dispensing devices. In collaboration with IDUs, we developed a preventive intervention consisting of four new preparation practices aimed at avoiding the use of syringes in the preparation, and reducing the contamination of the materials. This report describes the results of a pilot trial introducing the new practices to ascertain their adoption potential and their potential efficacy in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…For example, as one way to reduce overdose risk, overdose prevention programs recommend injecting a small dose of the drug (i.e., a test shot) to test its potency before self-administering the entire dose of a drug of unknown potency (Curtis & Guterman, 2009; Harm Reduction Coalition, 2000; 2012; Moore, 2004). IDUs may also clean their injection sites with rubbing alcohol, hand sanitizer, or soap and water prior to injecting to help reduce the likelihood of infections that may occur from bacteria on the skin entering the injector’s blood stream (Colon et al, 2009; Varga, Chitwood, & Fernandez, 2006). Other self-initiated harm reduction strategies include sterilizing used or borrowed injecting supplies with bleach and disposing of used injecting equipment in puncture-proof containers, both of which also reduce the likelihood of spreading infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as one way to reduce overdose risk, overdose prevention programs recommend injecting a small dose of the drug (i.e., a test shot) to test its potency before self-administering the entire dose of a drug of unknown potency (Curtis & Guterman, 2009; Harm Reduction Coalition, 2000; 2012; Moore, 2004). IDUs may also clean their injection sites with rubbing alcohol, hand sanitizer, or soap and water prior to injecting to help reduce the likelihood of infections that may occur from bacteria on the skin entering the injector’s blood stream (Colon et al, 2009; Varga, Chitwood, & Fernandez, 2006). Other self-initiated harm reduction strategies include sterilizing used or borrowed injecting supplies with bleach and disposing of used injecting equipment in puncture-proof containers, both of which also reduce the likelihood of spreading infections.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has also demonstrated that IDUs infrequently use other self-initiated harm reduction strategies, such as using a dropper to pour water into a cooker (instead of using possibly contaminated syringes to load water), drawing up drug mixtures with a preparation syringe, backload rinsing of syringes (Colon et al, 2009), and sterilizing needles with bleach (Fisher, Harbke, Canty, & Reynolds, 2002; Hawkins, Latkin, Mandel, & Oziemkowska, 1999; Nyamathi, Lewis, Leake, Flaskerud, & Bennett, 1995; Zapka, Stoddard, & McCusker, 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Following appraisal, one unpublished cross-sectional study was rejected [18]. The remaining studies - five cohort studies [19-23], one serial cross-sectional study [24], six cross-sectional studies [25-30] and one non-randomised intervention study [31] - were conducted in North America (11 in the USA [19-21,23,24,26-31] and two in Canada [22,25]) between 1992 and 2005 (Table 1). With one exception [30], all examined the association between use of an NSP (including secondary exchange of N/S [28]) or SIF [22] at which sterile non- N/S injecting paraphernalia were available, and the self-reported sharing of this equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The major methodological limitations identified include the use of convenience samples [20,25-28], self-reported exposure and outcome measures [19-30], the use of NSP (or SIF) as a proxy measure for use of sterile non- N/S injecting equipment [19-24,26-31], in some cases with inadequate assessment of exposure to NSP [20,27,28] and statistical analyses which failed to adjust for potential confounding variables [23,24,27,29,30] (Table 1). None of the cohort studies identified undertook traditional cohort analyses [19-23].…”
Section: Resultsmentioning
confidence: 99%
“…Various risk or harm reduction strategies and interventions have been proposed and/or tested to reduce high-risk practices for PWID who are not yet ready to stop injecting, including needle exchange, always using new needles to inject, bleach cleaning used needles, cleaning one’s skin with alcohol prior to injecting, rotating one’s injection site, and smoking/snorting rather than injecting, among others (Colon et al, 2009; Copenhaver et al, 2006; Des Jarlais et al, 2011; Hagan et al, 2000; Huo & Ouellet, 2007; Newmeyer, 1988; Phillips, Stein, Anderson, & Corsi, 2012). Risk reduction interventions range from self-initiated strategies to reduce individual harm to social/behavioral and community-level/public health interventions that target greater numbers.…”
Section: Introductionmentioning
confidence: 99%